Application of High Conductive Nanoparticles to Enhance the Thermal and Mechanical Properties of Wood Composite - Gupta, A. (Elsevier Ltd, 2018)
In the present work three different types of Nanofillers such as multiwalled carbon Nanotubes (CNTSs), aluminum oxide Nanoparticles and Nanosize activated charcoal were mixed with urea formaldehyde (UF) resin and used in the preparation of medium density fiberboard (MDF). The fillers has improved heat transfer during hot pressing and achieved proper curing due to enhanced thermos-physical properties of wood fibers. To improve the dispersion of Nanofillers into UF matrix, high speed mechanical stirring and ultrasonic treatments were used. The CNTSs were oxidized with nitric acid and the functional groups formed on its surface improved the dispersion and interaction with UF matrix. The mixing of CNTSs and Aluminum oxide with UF resin have reduced the curing time due to enhanced thermal conductivity of MDF matrix. The heat transfer during hot pressing of MDF improved significantly with the addition of CNTSs and Al2O3 Nanoparticle. The activated charcoal did not show much effect on heat transfer. The curing rate of UF resin improved with all the three Nanofillers, as the activation energy of UF curing decreases. The physical and mechanical properties of MDF have improved significantly with CNTSs and Al2O3 Nanoparticle. The activated charcoal has significantly decreased the formaldehyde emission of MDF. Â© 2018 Elsevier Ltd.